Microbial decomposition of longan leaf: I. physico-chemical and biological changes during composting - Kudreaung, Pattarin; Chromkaew, Yupa; Chinachanta, Kawiporn; Chaiwan, Fapailin; Shutsrirung, Arawan (Asia-Pacific Journal of Science and Technology, 2020)
Longan is an economic fruit crop of Northern Thailand. Incineration of longan residues from pruning is practiced, leading to environmental pollution. The more sustainable way is to convert the wastes into compost. In this study, therefore, composting of longan leaves was performed to monitor changes in physico-chemical and biological properties. There were three treatments including 1) longan leaves+cow dung (LC), 2) rice straw+cow dung (RC) and 3) longan leaves+rain tree leaves+cow dung (LRC). Our results indicated that, at day-120, adding rain tree leaves to longan leaves in LRC provided the lowest C:N ratio (24.2:1) while the highest one was found in LC (40.3:1). The high N applied treatments (LRC and LC) appeared to reach maturity germination index (GI) >80% earlier than that with low N content (RC). Humic acid concentration of RC and LC was around 4 times higher than their initial values, indicating high rate of humification process. The total N (TN) of all treatments tended to increase with composting time. The highest TN was recorded in LRC (2.7%) while RC gave the highest total P and K (0.25 and 2.99%, respectively). The bacterial population ranged from 2.2x106 to 2.6x108 colony forming unit (CFU)/g. The fungal population was low (» 106 CFU/g) at early stage of composting and afterwards the population increased to around 107 CFU/g. In contrast to bacteria and fungi, the number of actinomycetes was quite high (» 108 CFU/g). Bacteria, fungi and actinomycetes existing in the composts could be developed as a driving agent for rapid composting of longan leaves.